PTH-032 Mortality following ERCP for benign pathology in england between 2003 and 2015. (8th June 2018) - Harvey, Phil; Baldwin, Simon; Mytton, Jemma; Coupland, Ben; Evison, Felicity; Patel, Prashant; Trudgill, Nigel
Abstract : Introduction: Recent data on ERCP for the palliation of malignant biliary obstruction demonstrated high mortality and significant variation in outcomes between providers. We have therefore examined ERCP outcomes for in benign pathology. Methods: Hospital Episode Statistics (HES) include diagnostic and procedural data for all hospital attendances in England. HES is linked to the Office for National Statistics to provide mortality data. All subjects undergoing their first ERCP between 2003 and 2015 were included. Subjects with a relevant cancer diagnosis 2 years before, or after ERCP were excluded. Associations between demographics, co-morbidities, unit ERCP volume and mortality were examined by logistic regression analysis. Results: 2 01 851 subjects were included. 64.2% were female, median age 67 (IQR 51–79). 70.0%, 13.9% and 16.1% had a Charlson Co-morbidity score of 0, 1–4 and >4 respectively. A majority were during emergency admissions (53.5%). 7 day, 30 day and 12 month mortality was 0.8%, 2.3% and 8.0% respectively. 30 day mortality was 3.5% in emergency cases compared to 0.8% in elective. The re-admission rate within 30 days was 11.7%. Repeat ERCP was required within 90 days in 13.9%. 30 day mortality was positively associated with: male gender (OR 1.24 (95% CI:1.17–1.32), p<0.001), Black ethnicity (1.55 (1.12–2.14), p=0.008), Charlson co-morbidity score 1–4 (1.18(1.06–1.31), p=0.002), score >4 (3.55(3.31–3.81), p<0.001), increasing age quintile 47–62 (3.43(2.65–4.44), p<0.001), age 63–72 (7.01(5.48–8.97), p<0.001), age 73–81 (11.50(9.05–14.62), p<0.001) and age >81 (20.31(16.03–25.74), p<0.001). Factors associated with reduced mortality included; elective rather than emergency admission (0.37 (0.33–0.40), p<0.001), and day case procedures (0.86 (0.74–0.99), p=0.031). Advancing year of procedure 2004/05 (1.01(0.87–1.18), p=0.859, 2009/10 (0.71(0.61–0.83), 2014/15 (0.61, 0.53–0.71, p<0.001) was also associated with reduced mortality. Provider volume was not associated with mortality: volume knot 1 (1.00(1.00–1.00), p=0.445), knot 2 (1.00(1.00–1.01), p=0.253), knot 3 (0.99(0.98–1.01), p=0.288). Conclusions: 30 day mortality following ERCP for benign pathology is associated with advancing age, increasing co-morbidity and male gender. Outpatient elective procedures were negatively associated with mortality. Mortality has reduced in recent years, but no variation in mortality was observed based upon provider volume.